Nośność graniczna rozciąganych elementów o przekroju kwadratowym z wycięciami - Miastkowski, J. (Engineering Transactions, 1969)
This paper contains a theoretical and experimental analysis of the limit load of an element of square cross-section weakened by an angular notch and subject to tension. The PA-2 and PA-4 aluminium alloys were subject to experimental investigation. It is found that the agreement of the theoretical and experimental results is influenced in an essential manner by the kind of the material and the geometrical form of the notch and its depth.